On the absolute convergence of power series - Hembars'ka, S. B.; Zaderei, P. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We obtain a two-dimensional analog of the Hardy-Littlewood result on the absolute convergence of power series in the case of multiple series on the boundary of a unit polydisk.